2020
DOI: 10.2174/1568026620666200704135327
|View full text |Cite
|
Sign up to set email alerts
|

Shape-based Machine Learning Models for the Potential Novel COVID-19 Protease Inhibitors Assisted by Molecular Dynamics Simulation

Abstract: Background: The vast geographical expansion of novel coronavirus and an increasing number of COVID-19 affected cases has overwhelmed health and public health services. AI and ML algorithms have extended its major role in tracking the disease patterns, and in identifying possible treatment of disease. Objective: To identify potential COVID-19 protease inhibitor through shape-based Machine Learning assis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 168 publications
0
18
0
Order By: Relevance
“…Ligand-Receptor Docking was performed with Optimized Potential for Liquid Simulations (OPLS) algorithms to identify high affinity compounds. The selected drug candidates were subjected to Molecular Dynamic Simulations followed by absorption, distribution, metabolism, and excretion-toxicity in pharmacokinetics (ADMET) studies (AdmetSAR and Swiss ADME software explained various ADMET properties) and other analyses [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ligand-Receptor Docking was performed with Optimized Potential for Liquid Simulations (OPLS) algorithms to identify high affinity compounds. The selected drug candidates were subjected to Molecular Dynamic Simulations followed by absorption, distribution, metabolism, and excretion-toxicity in pharmacokinetics (ADMET) studies (AdmetSAR and Swiss ADME software explained various ADMET properties) and other analyses [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overall, diverse new repurposed drugs against the treatment of COVID-2019 were suggested in this systematic review through AI techniques [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ], such as: valrubicin, aprepitant, dihydroergotamine, * bivalirudin, eltrombopag, eribulin, fulvestrant, idarubicin, ivermectin, ledipasvir, lifitegrast, nystatin, regorafenib, trypan blue, vitamin E, ruxolitinib, nafcillin, nabumetone, octacosanol, cinametic acid, trabectedin, lauric acid, acorbyl palmitrate, palmidrol, salmeterol, simvastatin, guaifenesin, verteporfin, metergoline, rescinnamine, leuprolide, lusutrombopag, telotristat, fostamatinib, tofacitinib, etoricoxib, ziprasidone, interferon-gamma; cyclosporine, zidovudine, methotrexate, artemisinin, glycyrrhizin acid, quinine, suramin, albuterol, ciprofloxacin, spirapril, lisinopril, and captopril. …”
Section: Discussionmentioning
confidence: 99%
“…More importantly, the most potent compounds presented nanomolar concentration levels for a half-maximal inhibitory. Nayarisseri et al [ 122 ] proposed a shape-based ML method, which generates the 3D shaped pharmacophoric features of the seed compound. Furthermore, molecular docking was performed with optimized potential for liquid simulations (OPLS) algorithms to recognize high affinity compounds targeting M pro .…”
Section: Cadd Against Sars-cov-2: Targeting M Promentioning
confidence: 99%
“…They also found a novel compound ‘nCorv-EMBS’, which is not included in public chemical databases (PubChem, ZINC or ChEMBL) so far. The results of toxicity analysis suggested nCorv-EMBS was valuable to further research as the main protease inhibitor in COVID-19 [ 122 ].…”
Section: Cadd Against Sars-cov-2: Targeting M Promentioning
confidence: 99%
“…Based on computational hierarchical virtual screening, recently Wang showed that valrubicin alongside with other drugs, such as lopinavir and carfilzomib inhibits the main protease of SARS-CoV-2 ( Wang, 2020 ). Moreover, another report based on a machine learning simulation has recently shown that valrubicin is a potential COVID-19 protease inhibitor ( Khandelwal et al 2020 ). However, no considerations on the effective doses have been modeled: the clinical use as an agent for systemic administration is not validated, being approved only as a topic solution, and any speculation for the design of clinical trials should account for the adverse safety profile of this chemotherapeutic.…”
Section: Potential Anticancer Drugs For Covid-19mentioning
confidence: 99%